Analysis of Titanium Grade 2 Surface Roughness on Turning Process - Agus Harijono; AM Mufarrih; Nanang Qosim (Jurnal Teknik Mesin, 2021)
Titanium Grade 2 is a type of material that is often used in industry, especially in materials for biomedical implants. Titanium Grade 2 has a good stiffness to weight ratio, is corrosion resistant and has good biocompatibility in the body. However, it has a low thermal conductivity, so it is necessary to choose the right machining parameter to produce a good surface roughness value. This study aims to determine the characteristics of Titanium Grade 2, namely the surface roughness of the results of lathe machining. The research design used the Taguchi L9 method, with 2 factors and 3 levels. The machining parameters used are spindle rotation 500; 700; 900 rpm and feed speed 25; 50; 75mm/min. The response variable studied was surface roughness. The milling process is carried out using a Maximat V13 lathe. Surface roughness was measured using a Mitutoyo surface roughess tester. Data analysis used ANOVA analysis. The results showed that there was an effect of variations in machining parameters on the surface roughness response. The spindle rotation variable has a p-value of 0.039 and the feeding motion variable has a p-value of 0.025. This shows that the two independent variables have a significant effect on the surface roughness response. The lowest surface roughness can be achieved by setting the spindle rotation at 700 rpm and the feed speed at 25 mm/min.